Juvenile hormone-induced microRNA miR-iab-8 regulates lipid homeostasis and metamorphosis in Drosophila melanogaster. - He, Q.; Chen, S.; Hou, T.; Chen, J. (Insect Molecular Biology, 2024)
Metamorphosis plays an important role in the evolutionary success of insects. Accumulating evidence indicated that microRNAs (miRNAs) are involved in the regulation of processes associated with insect metamorphosis. However, the miRNAs coordinated with juvenile hormone (JH)-regulated metamorphosis remain poorly reported. In the present study, using high-throughput miRNA sequencing combined with Drosophila genetic approaches, we demonstrated that miR-iab-8, which primarily targets homeotic genes to modulate haltere-wing transformation and sterility was up-regulated by JH and involved in JH-mediated metamorphosis. Overexpression of miR-iab-8 in the fat body resulted in delayed development and failure of larval-pupal transition. Furthermore, metabolomic analysis results revealed that overexpression of miR-iab-8 caused severe energy metabolism defects especially the lipid metabolism, resulting in significantly reduced triacylglycerol (TG) content and glycerophospholipids but enhanced accumulation of phosphatidylcholine (PC) and phosphatidylethanolamine (PE). In line with this, Nile red staining demonstrated that during the third larval development, the TG content in the miR-iab-8 overexpression larvae was continuously decreased, which is opposite to the control. Additionally, the transcription levels of genes committed to TG synthesis and breakdown were found to be significantly increased and the expression of genes responsible for glycerophospholipids metabolism were also altered. Overall, we proposed that JH induced miR-iab-8 expression to perturb the lipid metabolism homeostasis especially the TG storage in the fat body, which in turn affected larval growth and metamorphosis.